CaLB Catalyzed Conversion of ε-Caprolactone in Aqueous Medium. Part 1: Immobilization of CaLB to Microgels - Stefan Engel; Heidi Höck; Marco Bocola; Helmut Keul; Ulrich Schwaneberg; Martin Möller (Polymers, 2016)
The enzymatic ring-opening polymerization of lactones is a method of increasing interest for the synthesis of biodegradable and biocompatible polymers. In the past it was shown that immobilization of Candida antarctica lipase B (CaLB) and the reaction medium play an important role in the polymerization ability especially of medium ring size lactones like ε-caprolactone (ε-CL). We investigated a route for the preparation of compartmentalized microgels based on poly(glycidol) in which CaLB was immobilized to increase its esterification ability. To find the ideal environment for CaLB, we investigated the acceptable water concentration and the accessibility for the monomer in model polymerizations in toluene and analyzed the obtained oligomers/polymers by NMR and SEC. We observed a sufficient accessibility for ε-CL to a toluene like hydrophobic phase imitating a hydrophobic microgel. Comparing free CaLB and Novozym® 435 we found that not the monomer concentration but rather the solubility of the enzyme, as well as the water concentration, strongly influences the equilibrium of esterification and hydrolysis. On the basis of these investigations, microgels of different polarity were prepared and successfully loaded with CaLB by physical entrapment. By comparison of immobilized and free CaLB, we demonstrated an effect of the hydrophobicity of the microenvironment of CaLB on its enzymatic activity.